RELATIONSHIP MARKETING : PARADIGMA BARU DALAM MEMPERTAHANKAN PELANGGAN - Rahmiati, Rahmiati (Faculty of Economics and Business Universitas Jenderal Soedirman, 2010)
Today, more companies recognize the importance of retaining current customers. Many markets have settled into maturity and there are not many new customers entering most categories. Competition is increasing and the cost of attracting new customers are raising. Offensive marketing typically cost more than defensive marketing, because it takes a great deal of effort and spending to coax satisfied customer away from competitors. The best approach to customer retention is make long-term mutual relationship through relationship marketing programme. Relationship marketing is cross-functional marketing. It is organized around processes that involve all aspect of the organization. This new marketing perspective focus on creating, maintaining and enhancing strong relationship with customers and other stakeholders with goal is to deliver long-term superior customer value more than its competitor.